1996
DOI: 10.1007/bf00377445
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced alterations in natural killer cell number and function

Abstract: To study the effects of exercise on natural killer (NK) cell number and activity (NKCA) healthy male (n = 32) and female (n = 32) subjects were randomly assigned to an exercise or control condition. Exercise involved a continuous incremental protocol consisting of cycling for three periods of 6 min at work rates corresponding to 55%, 70% and 85% peak oxygen uptake (VO2peak). Blood samples were drawn at baseline, at 6 min, 12 min and 18 min during exercise, and at 2 h following completion of exercise. Relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
2
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 25 publications
3
28
2
1
Order By: Relevance
“…The T-helper cell counts did not decline below resting values, which is in contrast to intense endurance protocols (Kajiura et al, 1995;Moyna et al, 1996). A negative correlation was observed between cortisol concentration and the increase in T-helper cell counts between baseline and 2 h of recovery.…”
Section: Discussioncontrasting
confidence: 71%
“…The T-helper cell counts did not decline below resting values, which is in contrast to intense endurance protocols (Kajiura et al, 1995;Moyna et al, 1996). A negative correlation was observed between cortisol concentration and the increase in T-helper cell counts between baseline and 2 h of recovery.…”
Section: Discussioncontrasting
confidence: 71%
“…In a series of preliminary studies, we selected the maximal workload that could be completed during the exercise task by the majority of CSCI subjects because both the intensity and duration of the exercise seem to influence the scale of the NK mobilization. Second, earlier studies reported an increase in NKCA and the proportion of NK cells after 6-min cycling exercise at 55% of VO 2 max in AB persons, 20 indicating that short-duration low-intensity exercise can significantly increase NK cell number and activity. Therefore, we expected an increase in NKCA in the selected exercise, which was in fact observed in our AB subjects.…”
Section: Discussionmentioning
confidence: 92%
“…We considered that the number of NK cells in peripheral blood that had been mobilized from the lymphatic system during exercise was equal to the number of NK cells moved to damaged tissue from peripheral blood in SCI subjects. Moyna et al 20 reported that since NK cells from the spleen and bone marrow during exercise were immature, their cytotoxic activity must be lower than that of circulating NK. Therefore, 2-h arm ergometer exercise in SCI subjects reduced NKCA although the number of NK cells did not decrease after exercise.…”
Section: Discussionmentioning
confidence: 99%